2021
DOI: 10.1038/s41598-021-00239-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the spatial distribution of primary tumors in the lung to develop new prognostic biomarkers for locally advanced NSCLC

Abstract: The anatomical location and extent of primary lung tumors have shown prognostic value for overall survival (OS). However, its manual assessment is prone to interobserver variability. This study aims to use data driven identification of image characteristics for OS in locally advanced non-small cell lung cancer (NSCLC) patients. Five stage IIIA/IIIB NSCLC patient cohorts were retrospectively collected. Patients were treated either with radiochemotherapy (RCT): RCT1* (n = 107), RCT2 (n = 95), RCT3 (n = 37) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Therefore, the 4‐feature signatures achieved a better generalization performance in head and neck cancer. Volume and TNM staging based signatures did not result in good performance on LUNG 4, which is consistent with published literature 52 …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the 4‐feature signatures achieved a better generalization performance in head and neck cancer. Volume and TNM staging based signatures did not result in good performance on LUNG 4, which is consistent with published literature 52 …”
Section: Resultssupporting
confidence: 91%
“…The LUNG 4 52 dataset consist of 322 advanced NSCLC or small cell lung cancer (SCLC) patients who received treatment at MAASTRO Clinic, The Netherlands. The 106 advanced cancer patients (TNM staging III, IIIa, and IIIb) for which clinical and survival information was available were included in this study—indices of included patients can be found in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of a link to anatomical location in this methodology would be interesting as little is known about tumour location and recurrence after SABR, as reports on disease spread to chest wall, mediastinum, bronchi, and vessels are limited to surgical cohorts ( 45 ). A quantitative assessment of location will provide more information than the tumour lobe location variable currently included in the models ( 46 , 47 ). Assessing specific anatomical locations such as ‘lungs only’ is a potential option to reduce spurious correlations but will lead to different amounts of data excluded dependent on location which could introduce bias.…”
Section: Discussionmentioning
confidence: 99%